2004
DOI: 10.1007/s10151-004-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

Manometric and clinical evaluation of patients after low anterior resection for rectal cancer

Abstract: The aim of this study was to examine the anorectal physiological and clinical changes that occur after low anterior resection for rectal cancer. Since 1998, 30 patients underwent laboratory tests of anorectal function, preoperatively and 1 month and 6 months after low anterior resection. Postoperatively all patients presented with increased bowel frequency, 60% of the patients with mild soiling and 30% with urgency for defecation. Six months after surgery there was a significant improvement of these symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 7 publications
7
22
0
1
Order By: Relevance
“…20 Manometric studies have revealed both the anal resting pressure and maximum squeeze pressure to worsen following TME surgery, with a reduced anal sensation and reduced physiologic rectoanal inhibitory refl ex (RAIR). 21,22 These observations support the concept that the RAIR depends on intramural colonic pathways. 23 A time-dependent recovery of the refl ex during the fi rst year after TME has been described, and it is assumed that the regeneration of the intramural nervous transmission across the anastomosis is responsible for that.…”
Section: Discussionsupporting
confidence: 60%
“…20 Manometric studies have revealed both the anal resting pressure and maximum squeeze pressure to worsen following TME surgery, with a reduced anal sensation and reduced physiologic rectoanal inhibitory refl ex (RAIR). 21,22 These observations support the concept that the RAIR depends on intramural colonic pathways. 23 A time-dependent recovery of the refl ex during the fi rst year after TME has been described, and it is assumed that the regeneration of the intramural nervous transmission across the anastomosis is responsible for that.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies about postoperative change of anorectal function demonstrated that the RAIR is stimulated by intramural nervous pathways. These nervous pathways might be injured during the dissection of the rectum, then the RAIR will be absent postoperatively [16,17]. However, two studies about the short-term preoperative change of anorectal function after nCRT demonstrated that the RAIR is present in all patients both before and after nCRT and there is no change in RAIR between them [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors should be identified that can be used to select patients likely to become incontinent. Previous studies generally agree that PRT is such a risk factor16–18, but differ with respect to the influence of other variables7, 12, 13, 19, 21–35.…”
Section: Introductionmentioning
confidence: 94%